GaInNAs double-barrier quantum well infrared photodetector with the photodetection at 1.24 μm - Ma, B. S. (2013)
A GaInNAs/AlAs/AlGaAs double-barrier quantum well infrared photodetector was grown by molecular beam epitaxy and fabricated by standard device processes. The growth structure of the as-grown sample was verified by x-ray diffraction measurement. The photoluminescence emission peak, which is related to the interband transition in the GaInNAs well, was observed at 1.2 eV. After annealing at 650 °C, a large blueshift of 40 meV was observed. The photocurrent peak at 1.24 m is associated with the intersubband transitions in the conduction band of the GaInNAs quantum well. The ten-band k· p calculations agree with the above observations.